Alternatively spliced form of angiopoietin-2 as a new vascular rheostat - Kamiyama, Miki; Augustin, Hellmut (Cancer research, 2021)
Angiopoietin (ANPGT)-TIE signaling serves as a critical regulator of vessel maturation controlling vascular quiescence, maintenance, and homeostasis (primarily through ANGPT1-TIE2 signaling), as well as enabling vascular plasticity and responsiveness to exogenous cytokines (primarily through antagonistically acting ANGPT2). An alternatively spliced form of ANGPT2 (ANGPT2443) was first reported 20 years ago. Yet, little is known to this day about its biological functions. In this issue of Cancer Research, Kapiainen and colleagues report an elegant series of experiments adding to the complexity and contextuality of ANGPT-TIE signaling. The authors studied the function of ANGPT2443 in cellular experiments as well as in a genetic model in vivo, revealing that it is proteolytically cleaved into a lower molecular weight isoform (termed ANGPT2DAP) that lacks the superclustering domain necessary for multimer formation. When compared with full-length ANGPT2, ANGPT2443 and ANGPT2DAP showed lower binding affinity to α5β1 integrin, but were more potent inhibitors of ANGPT1-TIE2 signaling. Functionally, ANGPT2443 impaired vessel enlargement and vein morphogenesis during postnatal retinal angiogenesis. Tumor experiments in Angpt2443-expressing mice showed enhanced destabilization of the lung vasculature, with varying effects on metastasis. Taken together, the study provides important insight into the significance of ANGPT2 alternative splicing and identifies ANGPT2443 and ANGPT2DAP as a biological rheostat of ANGPT1-TIE2 signaling. Future work will need to characterize the relative ratios and functional contributions of the ANGPT2 variants in different pathophysiologic settings. - See related article by Kapiainen et al., p. 129
Gesehen am 20.05.2021